2021
DOI: 10.1111/idh.12493
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the prevalence and predictors of workplace bullying towards the dental hygienist

Abstract: Workplace violence (WPV) is defined by the Workplace BullyingInstitute 1 as repeated, harmful mistreatment from one or more employees to an intended target(s) and includes threatening, humiliation or intimidation of the intended target; verbal, psychological or emotional abuse; and interfering with work duties. The U.S. Department of Labor 2 recognizes WPV as a hazard in the healthcare industry. The World Health Organization 3 states that WPV is a globally recognized problem, and between 8% and 38% of healthca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
3
2
0
Order By: Relevance
“…The report of sexual harassment by patients in this study was approximately 20%, which is significantly lower than findings of over 60% of dental hygienists reporting inappropriate patient sexual behaviour in the past 12 months by Patel et al 22 An international study found 25% of nurses experienced sexual harassment, which is more consistent with our findings; however, there are no data specific to male nurses 24 . In regard to workplace bullying, this sample reported 15%–20% had experienced bullying, similar to Petit et al's findings of 21% in a more general population of dental hygienists 23 . Intimidation by co‐workers and employers for male dental hygienists has not been reported in the literature for nursing or dental hygiene.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The report of sexual harassment by patients in this study was approximately 20%, which is significantly lower than findings of over 60% of dental hygienists reporting inappropriate patient sexual behaviour in the past 12 months by Patel et al 22 An international study found 25% of nurses experienced sexual harassment, which is more consistent with our findings; however, there are no data specific to male nurses 24 . In regard to workplace bullying, this sample reported 15%–20% had experienced bullying, similar to Petit et al's findings of 21% in a more general population of dental hygienists 23 . Intimidation by co‐workers and employers for male dental hygienists has not been reported in the literature for nursing or dental hygiene.…”
Section: Discussionsupporting
confidence: 88%
“…The topic of sexual harassment and workplace bullying among dental hygienists has been recently studied and shown to be an issue in the workplace, but given the small sample of males in these studies, it was not possible to make comparisons between males and females 22,23 22 An international study found 25% of nurses experienced sexual harassment, which is more consistent with our findings; however, there are no data specific to male nurses 24 .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The maximum commonplace form of insult turned into verbal abuse, it became suggested that experts are greater used to insult and misbehave with the junior students on the whole the house officials and clinical officers are the patients, absence of the anti-bulling policy at clinical schools and in hospitals are incurring the terrible and insulting behavior of senior medical doctors. (Petit et al 2021).…”
Section: Discussionmentioning
confidence: 99%